Certificates of Ownership without Warkah in Indonesia - Bayu Prasetyo; Ikhwanul Muslim; Rio Arif Pratama (Indonesian Journal of Law and Economics Review, 2019)
From the results of the study it can be seen that the issuance of certificate of ownership rights No. 317, 318, 320, 321, 322, 339, 340, 341 in Balikpapan City, eight of which certificates have no heritage and do not have strong legal force to the owners. Indonesia adheres to a negative publication system, but there is still an opportunity to file a lawasuit to the Court, meaning that the certificate of land rights is the strongest but not absolute. Then a certificate without a license does not have strong legal force if a claim is filed to the Court, while the efforts to submit a request for cancellation of the no-rights ownership certificate is by submitting a written request to the Balikpapan City Land Office and attaching copy of identity photocopy of certificate, photocopy of court decision, execution report and other documents related to cancellation. The court ruling was based on the Balikpapan City Land Office to issue a decision to cancel the certificate, in accordance with the ruling which had obtained permanent legal force.